FROM TRADITION TO TRANSFORMATION: Decontextualization of Dayah in Aceh's Millennial Context - Nasir, Mohd.; Rizal, Syamsul; Zainuddin, Zainuddin; Muhibuddin, Muhibuddin; Mulyadi, Mulyadi (Journal of Contemporary Islam and Muslim Societies, 2024)
Abstract: This study investigates factors contributing to the decontextualisation of dayah as an Islamic educational institution in Aceh. Qualitative research methods, including observation, interviews, and document review, were used to collect data and gain insights into this phenomenon. This study highlights three findings: first, an authoritarian relationship between teungku (Islamic scholars) and students hinders meaningful connection and engagement; second, the use of hierarchical teaching methods further reinforces this disconnection, limiting opportunities for collaboration and active learning; third, outdated facilities present challenges in modernising and adapting dayah institutions. By addressing these factors, dayah institutions can effectively restore their connection with Acehnese youth and foster a comprehensive and contemporary Islamic education. It is recommended that teungku in Aceh integrate technology into their teaching methods, ensuring relevance and appeal to the young generation. This study also shows the need for dayah institutions in Aceh to adapt to the evolving educational landscape and embrace technological advancements. This research contributes to the discourse on educational transformation in Aceh by providing insights into the challenges and potential strategies for revitalizing dayah institutions in the face of a changing educational milieu.Keywords: decontextualization, Islamic traditional learning, dayah, Aceh’s millineal